Sexually transmitted infections and reproductive tract infections in female sex workers - Shethwala Nimisha; Mulla Summaiya; Kosambiya J; Desai Vikas (Wolters Kluwer Medknow Publications, 2009)
The present study was conducted in 300 female sex workers (FSWs) from Surat city in 2005-2006. Vaginal swabs, endocervical swabs and serum samples were collected from each of these FSWs. Vaginal samples were screened for bacterial vaginosis (BV), candidiasis and Trichomonas vaginalis . Endocervical swabs were screened for gonococcal infection. Serological tests for human immunodeficiency virus (HIV), hepatitis B surface antigen (HBsAg) and syphilis were performed. From a total of 300 FSWs, BV was detected in 40 (13.33%), trichomoniasis in six (2%), candidiasis in 31 (10.33%), HIV seropositivity in 35 (11.66%), HBsAg reactivity in 10 (3.33%) and rapid plasma regain (RPR) reactivity in 20 (6.66%) cases. RPR-positive serum samples were confirmed by the treponema pallidum hemaglutination test. Gonococcal infection was not found in any of the FSWs. Of the total of 35 HIV-positive patients, 20 patients had associated coinfection. Of the 35 HIV-seropositive FSWs, BV was detected in six (17.14%), candidiasis in six (17.14%), syphilis in five (14.28%) and HBsAg in two (5.71%). One (2.85%) HIV-positive FSW was positive for both candidiasis and syphilis.